2022
DOI: 10.1002/advs.202200670
|View full text |Cite
|
Sign up to set email alerts
|

Cells‐Micropatterning Biomaterials for Immune Activation and Bone Regeneration

Abstract: Natural tissues are composed of ordered architectural organizations of multiple tissue cells. The spatial distribution of cells is crucial for directing cellular behavior and maintaining tissue homeostasis and function. Herein, an artificial bone bioceramic scaffold with star-, Tai Chi-, or interlacing-shaped multicellular patterns is constructed. The "cross-talk" between mesenchymal stem cells (MSCs) and macrophages can be effectively manipulated by altering the spatial distribution of two kinds of cells in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 52 publications
1
29
0
1
Order By: Relevance
“…[17,18] The amount of encapsulated macrophages was inspired by studies that show that the 2:1 ratio of MSCs cocultured with macrophages was more favorable to osteogenic differentiation of MSCs. [57][58][59] In most conditions, the ALP activity was significantly higher in TRI microcapsules (Figure 2c). ALP is considered an early marker of osteoblastic differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…[17,18] The amount of encapsulated macrophages was inspired by studies that show that the 2:1 ratio of MSCs cocultured with macrophages was more favorable to osteogenic differentiation of MSCs. [57][58][59] In most conditions, the ALP activity was significantly higher in TRI microcapsules (Figure 2c). ALP is considered an early marker of osteoblastic differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…Macrophage polarization (decisive for maintaining bone homeostasis) helps regulate the dynamic balance between bone tissue destruction and formation . Macrophage polarization manipulation toward M2 significantly promotes bone tissue regeneration, which is dominant among many factors . Therefore, for bone regeneration, biomaterials should shift from relative inertness to those with osteoimmunomodulatory properties, emphasizing efficient regulation of macrophage polarization toward M2.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 Zhang et al found that activating the Wnt/β-catenin signalling pathway mediated via the macrophage-derived paracrine signalling mediator (Wnt10b) could improve the osteogenic properties of mesenchymal stem cells. 56 This meant that alkalitreated scaffolds might directly activate the Wnt/β-catenin pathway of osteoblasts to enhance osteogenic differentiation, regulate macrophage polarization to act on osteoblasts via triggering the Wnt/β-catenin pathway of macrophages, or both. In general, the Wnt/β-catenin signalling pathway might participate in the signal transduction involved in hydrophilic surfacemodified PCL/HA scaffold-regulated osteogenesis.…”
Section: Papermentioning
confidence: 99%